Cochlear Implantation in Children with Autism Spectrum Disorder: A Systematic Review and Pooled Analysis. Issue 1 (2nd January 2022) - Mathew, Rajeev; Bryan, James; Chaudhry, Daoud; Chaudhry, Abdullah; Kuhn, Isla; Tysome, James; Donnelly, Neil; Axon, Patrick; Bance, Manohar
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To determine outcomes following cochlear implantation (CI) in children with autism spectrum disorder (ASD). Databases Reviewed: MEDLINE, Embase, Web of science, Cochrane Library, and Clinicaltrial.gov. Methods: The review was performed according to the PRISMA statement. Primary outcomes measures were changes in speech perception and speech production scores. Secondary outcome measures included communication mode, device use, parental recommendation of implant, postoperative hyperacusis, and quality of life measures. Pooled analysis of outcomes was performed if possible. Results: Twenty-four studies reported on 159 children with ASD. There were improvements in speech perception in 78% of cases and in speech expression in 63% of cases, though the extent of this improvement was variable. Seventy-four percent of children with ASD and CI are nonoral communicators. Intermittent/nonuse rate was 31%. Hearing outcomes are worse compared to children with other disabilities. The vast majority of parents would recommend CI based on their experiences. Conclusion: Outcome in children with ASD and CI are highly variable and significantly poorer compared to non-ASD children. Despite this, most parents report positive experiences and the evidence supports the use of CI in children with ASD.